Classification Of Image Corner Point Detection System To Identify A Shape Using The Viola Jones Method - Frencis Matheos Sarimole; Sopan Adrianto; Dedi Gunawan; Fiktor Kurnia Tafonao (International Journal of Computer Technology and Science, 2024)
Along with the times, computer technology is developing very rapidly. The increasingly rapid development of computer technology means that everyone is required to utilize computer technology in their daily lives. Utilization of technology is one of the implementation roles of scientific disciplines. The reason behind the formation of this research is so that in the future it will become a fun learning concept in the introduction of objects and shapes in children and the motor development of children. children are usually more interested in seeing pictorial text, or pictures that contain lots of color. The Viola Jones method itself was chosen as the research completion algorithm. The Viola Jones method is usually used as a method in research that discusses the detection of objects, faces and others. The Viola Jones method was chosen because it has a high level of accuracy that can reach 100% probability.